Efficient, Thermally Stable, and Mechanically Robust All‐Polymer Solar Cells Consisting of the Same Benzodithiophene Unit‐Based Polymer Acceptor and Donor with High Molecular Compatibility. Issue 5 (21st December 2020) - Lee, Jin‐Woo; Sun, Cheng; Ma, Boo Soo; Kim, Hyeong Jun; Wang, Cheng; Ryu, Jong Min; Lim, Chulhee; Kim, Taek‐Soo; Kim, Yun‐Hi; Kwon, Soon‐Ki; Kim, Bumjoon J.
Abstract: All‐polymer solar cells (all‐PSCs) are a highly attractive class of photovoltaics for wearable and portable electronics due to their excellent morphological and mechanical stabilities. Recently, new types of polymer acceptors ( P A s) consisting of non‐fullerene small molecule acceptors (NFSMAs) with strong light absorption have been proposed to enhance the power conversion efficiency (PCE) of all‐PSCs. However, polymerization of NFSMAs often reduces entropy of mixing in PSC blends and prevents the formation of intermixed blend domains required for efficient charge generation and morphological stability. One approach to increase compatibility in these systems is to design P A s that contain the same building blocks as their polymer donor ( P D ) counterparts. Here, a series of NFSMA‐based P A s [P(BDT2BOY5‐X), (X = H, F, Cl)] are reported, by copolymerizing NFSMA (Y5‐2BO) with benzodithiophene (BDT), a common donating unit in high‐performance P D s such as PBDB‐T. All‐PSC blends composed of PBDB‐T P D and P(BDT2BOY5‐X) P A show enhanced molecular compatibility, resulting in excellent morphological and electronic properties. Specifically, PBDB‐T:P(BDT2BOY5‐Cl) all‐PSC has a PCE of 11.12%, which is significantly higher than previous PBDB‐T:Y5‐2BO (7.02%) and PBDB‐T:P(NDI2OD‐T2) (6.00%) PSCs. Additionally, the increased compatibility of these all‐PSCs greatly improves their thermal stability and mechanical robustness. For example, the crack onset strain (COS) and toughness of the PBDB‐T:P(BDT2BOY5‐Cl) blend are 15.9% and 3.24 MJ m –3, respectively, in comparison to the PBDB‐T:Y5‐2BO blends at 2.21% and 0.32 MJ m –3 . Abstract : A new class of polymer acceptors ( P A s, P(BDT2BOY5‐X)) consisting of benzodithiophene (BDT) and non‐fullerene small molecule‐accepting units is developed, which shows excellent material compatibility with an efficient BDT‐based polymer donor ( P D ). The resulting all‐polymer solar cells show excellent photovoltaic efficiency, thermal stability, and mechanical robustness at the same time, benefitting from the high chemical and molecular compatibilities between P D and P A .